Warisan Sosial sebagai Salah Satu Fungsi Komunikasi Massa - Yopi Kusmiati (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Currently the mass media has become the need of almost everyone, which is not only consumed by adults, but by all circles, and also with children. Mass communication certainly provides information or messages to the audience about everything. Mass communication is a communication process conducted by communicators through mass media with the target is the public, so focus of mass communication studies is the media. There are many functions of mass communication, one of them is the function of social heritage. In the social heritage is also included the function of educating, providing information and cultural transmission. Because, if discussing about culture, it will include three of things: ideas, activities and objects of activity, are a part or element of social heritage. One example of the function of social heritage conveyed through the mass media is the “Jejak Rasul” program. Through the event, the television media pass on ideas to the audience (especially da'i as the next generation) to teach Islam to non-Muslims with the method used by Prophet Muhammad SAW, so the da'wah that will be delivered by da'i will succeed and reach the target, including the idea of ​​the formation of civil society which is also a legacy for the Islamic community to this day. The idea passed from generation to generation that further includes the culture, so that it functions also as a cultural transmission.